Post-Orthotopic Liver Transplant Cholangiopathy Assessment and Surveillance with Endoscopic Ultrasonography: The Way Forward - Gadour, Eyad; Hassan, Zeinab (International Journal of Innovative Research in Medical Science, 2023)
Post-orthotropic liver transplant (POLT) cholangiopathies are a group of biliary complications that develop after liver transplantation. These conditions can lead to significant morbidity and mortality if not detected and treated early. Traditionally, magnetic resonance cholangiopancreatography and computed tomography scan have been used to identify biliary complications after OLT. Hence, the current study aimed to evaluate the accuracy of endoscopic ultrasonography (EUS) in assessing and monitoring POLT cholangiopathies by performing a comprehensive review of the literature. Relevant articles published until February 2023 were searched from various databases including PubMed, Embase, and Cochrane Library. The search terms used were “endoscopic ultrasound,” “post-orthotopic liver transplantation,” “primary sclerosing cholangitis,” and “cholangiopathy.” Relevant articles were selected and included in this review. EUS has emerged as a state-of-the-art method for the assessment and surveillance of POLT cholangiopathies, with high success rates in diagnosing and treating biliary complications. In patients with primary sclerosing cholangitis, EUS can help in the early detection of primary tumors and biliary strictures and can be a guide in therapeutic interventions such as endoscopic retrograde cholangiopancreatography and biliary drainage. In conclusion, EUS has a superior diagnostic accuracy than other imaging modalities such as magnetic resonance cholangiopancreatography and computed tomography scan in detecting biliary complications after OLT.